ON SOME CHARACTERIZATION OF SUPERPARACOMPACTNESS, STRONG PARACOMPACTNESS AND COMPLETE PARACOMPACTNESS - I.N. Tillabaev (Новости образования: исследование в XXI веке, 2024)
In this paper, we study uniform analogs of complete paracompactness [1] strong paracompactness [2], and superparacompactness [3].